In China's wake : how the commodity boom transformed development strategies in the Global South - Jepson, Nicholas (Columbia University Press, 2020)
In the early 2000s, Chinese demand for imported commodities ballooned as the country continued its breakneck economic growth. Simultaneously, global markets in metals and fuels experienced a boom of unprecedented extent and duration. Meanwhile, resource-rich states in the Global South from Argentina to Angola began to advance a range of new development strategies, breaking away from the economic orthodoxies to which they had long appeared tied. In China's Wake reveals the surprising connections among these three phenomena. Nicholas Jepson shows how Chinese demand not only transformed commodity markets but also provided resource-rich states with the financial leeway to set their own policy agendas, insulated from the constraints and pressures of capital markets and multilateral creditors such as the International Monetary Fund. He combines analysis of China-led structural change with fine-grained detail on how the boom played out across fifteen different resource-rich countries. Jepson identifies five types of response to boom conditions among resource exporters, each one corresponding to a particular pattern of domestic social and political dynamics. Three of these represent fundamental breaks with dominant liberal orthodoxy -- and would have been infeasible without spiraling Chinese demand. Jepson also examines the end of the boom and its consequences, as well as the possible implications of future China-driven upheavals. Combining a novel theoretical approach with detailed empirical analysis at national and global scales, In China's Wake is an important contribution to global political economy and international development studies.--